Off-clamp robot-assisted nephron-sparing surgery is associated with less operative time and potential for vascular complication in the treatment of renal angiomyolipoma > 4 cm: a comparative study - Yue Xue; Guoling Zhang; Haoxun Zhang; Jiuliang Wang; Zhixing Jiao; Guang Jia; Ao Qi; Yipeng Yu; Yiwen Liu; Bowen Wang; Feng Xiong; Chunyang Wang (BMC Urology)
Abstract Background Off-clamp robot-assisted nephron-sparing surgery (NSS) has emerged as a viable option for most localized renal carcinomas. However, its application in > 4 cm renal angiomyolipoma (RAML) is still challenging, and its safety and efficacy merit further investigations. This paper aims to compare perioperative parameters of RAML > 4 cm between off-clamp and on-clamp robot-assisted NSS using single-center data. Methods From September 2022 and February 2025, 55 patients who underwent robot-assisted NSS for RAML > 4 cm from the First Affiliated Hospital of Harbin Medical University were included in the retrospective study. Among these patients, 28 underwent off-clamp robot-assisted NSS (Offc-RAPN group), while 27 underwent on-clamp robot-assisted NSS (Onc-RAPN group). Baseline characteristics and perioperative outcomes were collected and assessed. Results All patients successfully underwent robot-assisted NSS, and none of them experienced conversion to open surgery or nephrectomy. Additionally, none in Offc-RAPN group converted to renal hilar clamping. The two groups manifested no significant differences in baseline characteristics. Compared to Onc-RAPN group, Offc-RAPN group exhibited shorter operative time, while showing comparable serum creatinine (Scr) change, estimated glomerular filtration rate (eGFR) change, hemoglobin (Hb) change, postoperative length of stay (PLOS), estimated blood loss (EBL) and rate of minor complications. Conclusions Off-clamp robot-assisted NSS offers shorter operative time and less potential for vascular complication than on-clamp robot-assisted NSS without increasing PLOS, EBL, and other complications. Hence, off-clamp robot-assisted NSS may be a safe and feasible approach for > 4 cm RAML.